Residents' acceptability and response to the water-pricing policy to reduce marine pollution caused by domestic sewage - Xu, Zhihua; Wang, Chuwei; Li, Shuqin; Shan, Jingzhu (Frontiers in Marine Science, 2023)
Domestic sewage has huge negative impacts on the marine environment. This paper discusses whether residents can accept the water-pricing policy that collects funds to improve sewage treatment technologies to reduce marine pollutants by raising water prices. First, the contingent valuation method is used to elicit residents’ acceptability of a water-price increase. Second, the contingent behavior method is applied to observe residents’ responses to the pricing policy. The results show that residents can accept an increase of 0.90 CNY/m3 in water price on average in Qingdao, China. We also find that people with low income show low acceptability of the water-pricing policy. Additionally, the water price plays a positive role in promoting residents’ willingness to reduce water use. The information transmission will encourage people to adopt water-saving behavior and strengthen the impact of the water-pricing policy on water-saving behavior. This paper provides important implications to establish a water-pricing policy to reduce the negative impacts of domestic sewage on the marine environment.